Toward a watershed in takaful dispute resolution: from litigation to effective dispute management - Oseni, Umar Aimhanosi (2014)
The recent years have seen significant progress in the takaful industry with a strong double-digit growth of 16% amounting to US$11 billion global gross takaful contributions in 2012. In order to sustain this growth and enrich its legal landscape, there is a need to examine the feasibility of effective dispute resolution mechanism for the takaful industry while drawing some lessons from the conventional insurance industry. This does not undermine the significance of the relevance of Islamic law in designing suitable models of enforceable dispute resolution mechanisms. While using qualitative legal analysis which predominantly adopts content analysis of current trends in takaful and insurance litigation, this paper finds that effective dispute resolution processes such as arbitration and mediation could be adapted to suit the specific needs of Shariah dispute resolution in the takaful industry. This would allow for cost-effective settlements that will guarantee existing business relationship among the parties and prevent unnecessary bad publicity in a highly competitive global insurance industry.